ASA DALAM ALUNAN GULA GENDING : STUDI TENTANG PANDANGAN MASYARAKAT DESA KEMBANG KERANG DAYA TENTANG PENDIDIKAN - Inderasari, Oryza Pneumatica; Fatoni, Haerul Rizal; Maulana, Ikmal; Sopian, Muhammad Ali (Journal of Urban Sociology, 2021)
Poverty, for some people, is not always followed by low education. This is evidenced by the experience of the gula gending sellers who can send their children to higher education. This research was completed using a qualitative descriptive method with the help of the social construction theory of Peter L. Berger and Luckman. Sources of data used are primary and secondary data. Bringing up the title "Asa in the strains of Gula Gending: A Study of the Views of the People of Kembang Kerang Daya Village on the Ability of Gula Gending Sellers to Send Children to Higher Education", describing the limitations of parents in terms of education, skills, and access to employment, has actually become a motivator for parents to change the future for the better. Children are believed to be an investment in the future, both in the hereafter and in the world, for gula gending sellers, so educating them to have a strong motivation in education is part of worship and struggle. In the results and conclusions, we describe the discussion: (1) gula gending in Kembang Kerang Daya Village, (2) the seller of gula gending and children's education, (3) the views of the people from Kembang Kerang Daya Village on the ability of the gula gending seller to send their children to higher education. And (4) the potential for culture and education that can be a potential for community empowerment.Â Keywords: Sellerâ€™s Expectations, Gula Gending, The Meaning of Education